Current Problems of Teaching Philosophical Disciplines in Educational Institutions of Slovak Republic - Ambrozy, Marián (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The paper is a brief mapping of the situation in the field of didactics of philosophy in the Slovak Republic. We observe that, despite almost three decades of separation of official philosophy from the dominance of Marxist philosophy, there is no satisfactory basis for the didactics of philosophy. The discipline Didactics of philosophy is represented by improvising several enthusiasts instead of developing serious theoretical foundations. We try to post a few recommendations that belong to all who want to seriously deal with the didactics of philosophy. The most important of them is the establishment of the Slovak scientific journal of didactics, the establishment of the organization of trade didactics, the separation of philosophy from other core subjects and the accreditation of the third level of university education in didactics of philosophy. The author convincingly proves the need to introduce knowledge of philosophy in school, since it will help teach students to think better, apply knowledge more effectively, critically evaluate everyday life, including relationships with parents, teachers, classmates and others. The article emphasizes that the experience of philosophizing will allow students to express their thoughts in writing, as well as to explore at an accessible level “eternal” issues of metaphysics, epistemology, natural philosophy, philosophy of history, philosophy of culture, philosophy of law, philosophical anthropology. philosophy of politics, etc. The urgency of impoving the teacher's competence in teaching this subject at school, in particular, updating the methodological support, substantiation of educational innovations for the use in the study of philosophy, as well as the introduction of ICT in the educational process are substantiated.